The Puncoviscana Formation of northwest Argentina: U-Pb geochronology of detrital zircons and Rb-Sr metamorphic ages and their bearing on its stratigraphic age, sediment provenance and tectonic setting - Adams, Christopher J. (2008)
U-Pb ages of detrital zircons from greywacke, and Rb-Sr metamorphic ages of slate from the Puncoviscana Formation of northwest Argentina are reported, and used to constrain the depositional age, metamorphic history, and sedimentary provenance of these rocks. The detrital zircon ages define mainly Late Mesoproterozoic-Early Neoproterozoic (1150-850 Ma) and Late Neoproterozoic-Early Cambrian (650-520 Ma) populations, the relative proportions of which vary inversely with the age of the youngest zircons in the samples. The 1150-850 Ma population is present in all samples and dominates in those with relatively old grains (> 600 Ma) in the Late Neoproterozoic-Early Cambrian population. However, the Late Mesoproterozoic-Early Neoproterozoic population is substantially smaller in those samples in which the Late Neoproterozoic-Early Cambrian population dominates and contains relatively young grains (> 520 Ma). The youngest zircons, c. 520 Ma, are in the Rancagua (Cachi, Salta province) sample. They form a narrow, unimodal peak and may have originated from volcanic sources active during deposition, in which case these youngest zircons would constrain the depositional age of the sample to the late Early Cambrian. This is consistent with Rb-Sr ages of 550-500 Ma for samples of slate from the Puncoviscana Formation. The detrital zircon age populations suggest a sedimentary provenance in a continental hinterland with a stabilized, extensive Late Mesoproterozoic orogen (with minor Paleoproterozoic and Archean precursors) and a more variable Late Neoproterozoic orogen containing an evolving sequence of less extensive subcomponents. A direct relationship with the Brazilian Shield is thus suggested with sedimentary detritus originating within the active-margin orogens of the interior, but with ultimate deposition in the passive-margin environment of western Gondwanaland. ©2008 E. Schweizerbart'sche Verlagsbuchhandlung.